2016
DOI: 10.1097/dcr.0000000000000644
|View full text |Cite
|
Sign up to set email alerts
|

Progression From Perianal High-Grade Anal Intraepithelial Neoplasia to Anal Cancer in HIV-Positive Men Who Have Sex With Men

Abstract: HIV-positive men who have sex with men should be monitored for perianal high-grade intraepithelial neoplasia. Those with high-risk features for the development of anal cancer may need more aggressive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…For HRA to be successful as a cancer prevention strategy, it needs to be both effective and tolerable to the target patient population. While previous studies have examined the clinical utility and performance of HRA [11,[14][15][16][17][18][19][20][21], few have documented patient experience with HRA, including the tolerability of discomfort during the procedure and postprocedure pain, as well as patient willingness to undergo routine or follow-up HRA [14,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…For HRA to be successful as a cancer prevention strategy, it needs to be both effective and tolerable to the target patient population. While previous studies have examined the clinical utility and performance of HRA [11,[14][15][16][17][18][19][20][21], few have documented patient experience with HRA, including the tolerability of discomfort during the procedure and postprocedure pain, as well as patient willingness to undergo routine or follow-up HRA [14,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Progression from anal HSIL to cancer was also reported to be high in another study. 7of 38 patients (18%) followed in Toronto Canada with perianal HSIL developed anal cancer, with a progression rate of 6.9 cases of anal cancer per 100 person-years of follow-up (7). …”
Section: Introductionmentioning
confidence: 99%
“…Anal intraepithelial neoplasia (AIN) is dysplasia in the epithelium of the anus and is a pre‐malignant condition associated with a low rate of progression to invasive squamous cell carcinoma (SCC) . The Bethesda system (2001) defines AIN I as low grade dysplasia with nuclear abnormalities confined to the lower third of the mucosa, also known as low grade squamous intraepithelial lesion.…”
Section: Introductionmentioning
confidence: 99%
“…The overall incidence of anal SCC is rare (0.9/100 000) but studies have demonstrated an increasing incidence in recent decades. There is a noticeable increase of AIN and SCC in the human immunodeficiency virus (HIV) population and men who have sex with men (MSM) . It is reported that in MSM, the incidence is 35/100 000 and if they are HIV positive with MSM the rate is significantly higher at 144/100 000, while the prevalence of AIN in HIV positive MSM is 29.1% and HIV negative MSM is 21.5% .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation